Comprehensive prediction of potential spatiotemporal distribution patterns, priority planting regions, and introduction adaptability of Elymus sibiricus in the Chinese region - Huan-Huan Lu; Yu-Ying Zheng; Yong-Sen Qiu; Liu-Ban Tang; Yan-Cui Zhao; Wen-Gang Xie (Frontiers in Plant Science)
The natural grassland in China is facing increasingly serious degradation. Elymus sibiricus L., as an important native alpine grass, is widely used in the restoration and improvement of natural grassland. In this study, the geographical distribution and environmental data of E. sibiricus in China were collected, and the potential spatiotemporal distribution pattern, planting pattern, and introduction adaptability of E. sibiricus were comprehensively predicted by using ensembled ecological niche model and Marxan model. The results show that (1) the potential spatial distribution of E. sibiricus mainly spans 33°–42°N and 95°–118°E. It was widely distributed in Qilian Mountains (northeast of Qinghai-Tibet Plateau), Taihang Mountains (junction of Loess Plateau and Inner Mongolia Plateau), and Tianshan Mountains; (2) with the passage of time, the suitable distribution regions of E. sibiricus generally showed a collapse trend, but its main distribution regions did not show obvious change, and the suitable regions (centroid) generally migrated to the southwest of China by 2.93 km; (3) the spatial distribution of E. sibiricus in the current period was significantly affected by the annual range of monthly near-surface relative humidity, mean annual air temperature, annual range of monthly potential evapotranspiration, mean monthly potential evapotranspiration, annual range of monthly climate moisture index, elevation, exchangeable Ca2+, available P, mean monthly near-surface relative humidity, exchangeable H+, and annual precipitation amount, respectively; (4) the potential planting area of E. sibiricus cover 2.059 × 105 km2, which was mainly distributed in Qilian Mountains (northeast of Qinghai-Tibet Plateau), Taihang Mountains (southeast of Inner Mongolia Plateau), the middle part of Tianshan Mountains, and the southeast of Altai Mountains; (5) the introduction adaptability regions of six E. sibiricus germplasm (LM01–LM06) were all distributed in the high-elevation regions of western China. The study aims to provide an effective theoretical basis for the collection, preservation, and utilization of E. sibiricus germplasm resources in China.